FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN ASFIKSIA NEONATORUM PADA BAYI DI RSUD KABUPATEN TAPANULI SELATAN TAHUN 2018 - F.Lubis, Tapi Endang; Batubara, Novita Sari (Universitas Aufa Royhan, 2020)
Asphyxia is a newborn emergency in the form of respiratory depression that continues causing various complications. In South Tapanuli District Hospital there are still many cases of asphyxia neonatorum, so researchers are interested in choosing this title. This research method is analytical research method with case series approach that aims to identify factors related to the incidence of asphyxia neonatorum in infants in South Tapanuli District Hospital 2018. The population of this study are all babies with asphyxia neonatorum based on the diagnosis of births in RSUD South Tapanuli Regency which is 113 people in January - December of 2016. The sample is the whole of the population to be sampled that is as many as 113 people. The sampling technique is done by total sampling method. The result of statistical test showed that there was a correlation between the age of the mother and the incidence of asphyxia neonatorum (p = 0.027), there was a correlation between the age of pregnancy with the incidence of asphyxia neonatorum (p = 0.026), and there was a relationship between parity and neonatorum asphyxia event (p = 0.001). It is desirable for health workers to further improve maternal health counseling about diseases and complications that can arise during pregnancy, childbirth and childbirth as a preventive effort against the occurrence of asphyxia neonatorum.